Application of the Concept of Socio-Cultural Integration in the Analysis of Deviance and Labeling Process - Bilinović, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
This paper discusses the concept of socio-cultural integration as a key concept for understanding the ways in which deviance and the labelling process take place within different social contexts, particularly within the small- scale social units in simple societies, and social units of small and large-scale in complex societies. In a theoretical sense, this paper is based on the conceptual legacy of cultural criminology, labelling theory and socio-anthropological and ethnographic studies on the subject of deviance and the labelling process. Featured contents on the topic of deviance and labelling processes are governed by the criterion of increasing level of socio-cultural integration, with the assumption that the processes that exist in small-scale social units in simple societies will be found in approximately equal social units in complex societies. Theoretical findings suggest that interdependence, as a strong feature of social relations among members of social units of small-scale societies, inhibits the labelling of individuals as deviants. An individual often contributes significantly to a smaller community and is usually associated with other members of the community by numerous interpersonal and kinship ties. Labelling such a member as deviant reduces or eliminates their social participation, which risks creating divisions and conflicts that disturb the social order. In contrast, the individual contributions of the majority of members of a large-scale social unit are of minor importance for the collective, and their relative independence reflects the absence of all-pervasive kinship ties. In this case, labelling people as deviant costs the social unit very little, either in terms of social contribution or in terms of risk to social integrity.